Tbx18 and the fate of epicardial progenitors. - Christoffels, V; Grieskamp, T; Norden, J; Mommersteeg, M; Rudat, C; Kispert, A (2009)
Uncovering the origins of myocardial cells is important for understanding and treating heart diseases. Cai et al. suggest that Tbx18-expressing epicardium provides a substantial contribution to myocytes in the ventricular septum and the atrial and ventricular walls. Here we show that the T-box transcription factor gene 18 (Tbx18) itself is expressed in the myocardium, showing that their genetic lineage tracing system does not allow conclusions of an epicardial origin of cardiomyocytes in vivo to be drawn.